THE INTERNSHIP IN ACCOUNTING EDUCATION. - Smith, C. Aubrey (The Accounting Review, 1964)
Any one who has been closely associated with accounting employment during the past two or more decades readily senses that the internship as a basic program has lost vitality. One of the reasons given for this loss of interest is the demand for accounting-trained graduates has created a situation whereby undergraduate students no longer need the contact provided by the internship to secure a permanent position. Many of the students are married and thus find it inconvenient to shift families from classroom to field and back to classroom. Many universities are on the semester plan which may not be conducive to an internship program. Many accounting firms for reasons best known to themselves are less responsive to accepting undergraduate students for organized internship programs today than in earlier years. Visual educational techniques and other improvements in teaching methods and materials may tend to reduce the necessity for field experience. On the assumption therefore, that the accounting internship is not dead or even moribund, this article tries to bring it up to date and implement it definite working rules.